2018
DOI: 10.26504/bkmnext364
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring report on integration 2018

Abstract: Ireland's population is growing ever more diverse. Almost 12% of people living here have a nationality other than Irish. We have seen a large increase in recent years in people choosing to become Irish citizens and in addition, the numbers of second generation migrants continue to grow. This increasing diversity offers many benefits to our communities-from enhancing our skills base to enriching our cultural life. When we truly value diversity and take steps to demonstrate that value, we send a powerful message… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(89 citation statements)
references
References 23 publications
5
82
0
Order By: Relevance
“…Previous research has also shown that the experience of people from the UK living in Ireland differs from that of other EU nationals (e.g. Barrett et al, 2006;McGinnity et al, 2018a). We look separately at those with poor English-language proficiency because this has been shown to be a crucial factor in migrant integration.…”
Section: Executive Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has also shown that the experience of people from the UK living in Ireland differs from that of other EU nationals (e.g. Barrett et al, 2006;McGinnity et al, 2018a). We look separately at those with poor English-language proficiency because this has been shown to be a crucial factor in migrant integration.…”
Section: Executive Summarymentioning
confidence: 99%
“…This concentration in areas with high private rented accommodation is likely driven by low levels of home ownership among migrants themselves (see McGinnity et al, 2018a). Given the current dysfunctional state of Ireland's private rented sector, with steeply rising rents and high levels of homelessness, migrant concentration in this type of tenure is problematic from an integration perspective.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…Respondents born outside of Ireland report, on average, much more positive attitudes towards immigrants than the Irish-born population (results available from the authors). See also McGinnity et al (2013), Chapter 6.…”
Section: Surveymentioning
confidence: 99%
“…A comprehensive series of education and training programmes on The Migrant Integration Strategy could provide support for policy development, and public bodies should be provided with resources and practical assistance in the policy development process. The establishment of an integration forum could provide a platform for public bodies to share experience and learn from best practice, and to better explore the links between integration policy and integration outcomes (for the most recent report on indicators and outcomes, see McGinnity et al, 2018). This would complement the existing Migrant Integration Strategy Monitoring and Coordination Committee, which is comprised of public sector and civil society representatives and other stakeholders, and is responsible for, among other things, overseeing implementation of The Migrant Integration Strategy and agreeing indicators for monitoring progress (Arnold et al, 2019, p. 16).…”
Section: Resultsmentioning
confidence: 99%
“…The European Agenda for the Integration of Third-Country Nationals was agreed in 2011 (Garcés-Mascareñas & Penninx, 2016, pp. 2-3), followed by the publication of an Action Plan on the Integration of Third-Country Nationals in 2016(McGinnity et al, 2018. In addition to the MIPEX assessment of integration policies, the Zaragoza indicators provide an agreed set of indicators that allow immigrant integration outcomes to be measured across the EU and the OECD (Huddleston et al, 2013).…”
Section: Introductionmentioning
confidence: 99%